Pengabdian Masyarakat di Era Pandemi Covid-19 di Curugbitung Nanggung Bogor - Salwa Aini Febrianti; Dedi Junaedi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2022)
The Community Empowerment Program is a form of student service for the community. This year the PPM implementation is different from the previous year due to the impact of Covid-19. This year's PPM aims to provide opportunities for students how students can participate in building public awareness for the prevention of Covid-19 transmission and provide public understanding to enter the New Normal while still complying with the Covid-19 health protocol and the provisions of life behavior during the New Normal. For two months, PPM activities carried out included: population data collection, counseling about the dangers of Covid-19, socializing the importance of maintaining cleanliness and health during the pandemic, distributing masks and providing information on the importance of wearing masks, as well as interviews about the impact of Covid-19 on the economy of the community. trader.